POLA KOMUNIKASI DALAM ORGANISASI PEMERINTAH DESA MUSUK KABUPATEN BOYOLALI DALAM MENINGKATKAN KINERJA PEGAWAI - Luthfiyathul Munawwaroh; Estu Widiyowati (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
This research is motivated by the phenomenon of the important role of organizationalcommunication in ensuring good coordination between employees and increasing theeffectiveness of the implementation of work programs designed by the village government. Thepurpose of this study is to analyze how the application of organizational communication inimproving employee performance at the Musuk Village Government Office, Boyolali Regency.This study uses Effendi's (2008) communication pattern theory as a research reference using adescriptive qualitative research method. The sampling technique used was purposive sampling.Data collection was carried out through interviews with the village head, village secretary andhamlet heads of Musuk village as well as documentation related to the performance of Musuk village government employees. The validity testing technique used by the researcher was sourcetriangulation. The results of the study indicate that the application of various communicationpatterns was able to improve the performance of Musuk village government employees, whichwas characterized by increased productivity, service quality, responsiveness, responsibility andaccountability of Musuk village government employees. Thus, the application of communicationpatterns carried out by the Musuk village government has been able to strengthen internalcommunication while optimally building a positive work culture within the Musuk villagegovernment environment.Keywords: Organizational Communication, Communication Patterns, Employee Performance